Uma leitura tradutória do conto "The paper menagerie", de Ken Liu, para o português brasileiro - Mackowiak, Maria Luísa (2022)
In this study, a translation project is presented of the short story “The Paper Menagerie”, by Ken Liu, a Chinese-American author, creating a translation to Brazilian Portuguese and later an analysis and a reflection about elements that relate to the neofantastic, to the culture and to the search for a translation with foreignizing characteristics. As the short story does not have a translation to Brazilian Portuguese, only to Portuguese from Portugal, the translation in this work comprehends English as the source language and Brazilian Portuguese as target language. First, the Polysystem Theory, by Itamar Even-Zohar (1990), specifying some aspects about the life, the works and the literary aesthetics of Ken Liu in the source literary polysystem. In addition, some information about the short story “The Paper Menagerie” was specified and a survey was carried out about translations related to fifteen different literary polysystems, as well as magazine covers and pictures related to the translations. Afterwards, the culture inside the short story and its context are explained through the theoretical perspectives by Andre Lefevere (2007) concerning to the translation of the other. Subsequently, Paulo Henriques Britto (2012) and Caetano Galindo (2015), translators and theorists from the Translation Studies as Lefevere, assist in the comprehension of the translator’s role in a way their work keep open the possibilities for an interpretation by the reader and preserves the semantic chain intended by the author of the source text. Thus, Lawrence Venuti (1995; 2002), also a translator and theorist, approaches the concept of a foreignizing translation, as it enables the translator to lead the reader to the author. Therefore, the translator of this work sought to make a translation using a foreignizing perspective, configuration that is accomplished during the reflection about the translation of the short story. The studies from the theorists Tzvetan Todorov (1981) and David Roas (2014) are approached to consider the fantastic segments, mainly those represented by the live origamis, and the neofantastic by Roas is defined in a way that some neofantastic characteristics are seen in Ken Liu’s short story. Afterwards, the Translation Studies are explained related to the strategies to describe the translation “O menagerie de papel”, using the studies by Rafael Lanzetti et al. (2009), with the translation technical strategies, by Antoine Berman (2007) and Caroline Paganine (2019), about the chain of signifiers, as well as the research by Mona Baker (2018), approaching the lexical and thematic networks in translation. The technical strategies were applied to stablish what tools were used in the search for a translation with foreignizing characteristics, noticing that the maintenance of the signifiers related to the neofantastic thematic networks, the culture and the movement of the paper animals, were preserved, along which the challenges of the translation act from Brazilian Portuguese to English were identified because of syntactic, lexical and pragmatical issues.